Cross-border M&A motives and home country institutions: Role of regulatory quality and dynamics in the Asia-Pacific region - Peter Zámborský; Zheng Joseph Yan; Erwann Sbaï; Matthew Larsen (Journal of Risk and Financial Management, 2021)
The purpose of this paper is to analyze the relationship between home country institutions and cross-border merger and acquisition (M&A) motives of MNEs from the Asia-Pacific region, with a focus on the role of regulatory quality and dynamics. We empirically examine how M&A motives are affected by elements related to risk of the institutional environment of the acquiring firm's home country regulatory quality over time. The study is grounded in the general theory of springboard MNEs, and the institutional views of cross-border operations, namely the institutional escapism and institutional fostering perspectives. Using data on over 700 cross-border M&As of European firms by Asia-Pacific MNEs in 2007-2017, we analyze the rationales for these deals and their relationship to the institutional characteristics of the buyers' home countries including regulatory quality and voice and accountability. We found that the quality of home country regulatory environment is significantly related to domestic firms' motivation for international M&As. However, the significance and sign of the effects differ for different types of motives and over time. Our findings contribute to the literature on general versus emerging MNE-specific internationalization theories (particularly the theory of springboard MNEs) by expounding on the types and dynamics of cross-border M&A motives.
Keywords: 330; cross-border merger and acquisition; emerging market multinational enterprise; home country institutions; internationalization; M&A motives; regulatory risk; springboard MNEs